Intensification of maize-based farming: What happened to the maize green revolution? - De Groote, Hugo (International Food Policy Research Institute, 2023)
Maize is the major food crop in eastern and southern Africa, including Kenya. Maize-based farming systems make up the largest proportion of agricultural land, and maize is central to the food system, in both rural and urban areas. Because of its importance, maize has received wide attention from the government, including in policy and research. As a result, Kenya has been at the forefront of the “maize green revolution” in Africa (Hassan and Karanja 1997; Hassan, Njoroge et al. 1998c). It was one of the first countries in Africa (with South Africa and Zimbabwe) to develop its own maize hybrids and combine them with fertilizer in demonstration trials, demonstrations, and dis semination (Hassan and Karanja 1997). In both South Africa and Zimbabwe, the settler communities continued to dominate commercial maize production (Eicher 1995), but in Kenya, indigenous African farmers took over most of the maize production right after independence.